2020
DOI: 10.4236/ojml.2020.106048
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Interactional Metadiscourse in English Travel Blogs

Abstract: With the development of tourism industry in internet plus era, travel blogs have become the main form of travel recording. Regarded as a valid device to intrude readers and to construct interaction between the writers and their readers, interactional metadiscourse is adopted widely. The study builds a corpus which consists of 30 English travel blogs. By calculating the occurrences and analyzing the functions of interactional metadiscourse, the study chooses qualitative and quantitative analysis to indicate how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Studies have nevertheless found that interactive metadiscourse, especially self-mentions and reader addresses, have prominent functions in online genres such as opinion blogs (Biri, 2017), travel blogs (Huang et al, 2020), and online customer reviews (Vásquez, 2015). Therefore, the study of reflexive metadiscourse should also be expanded to informal genres.…”
Section: The Scope Of Metadiscoursementioning
confidence: 99%
“…Studies have nevertheless found that interactive metadiscourse, especially self-mentions and reader addresses, have prominent functions in online genres such as opinion blogs (Biri, 2017), travel blogs (Huang et al, 2020), and online customer reviews (Vásquez, 2015). Therefore, the study of reflexive metadiscourse should also be expanded to informal genres.…”
Section: The Scope Of Metadiscoursementioning
confidence: 99%
“…According to Hyland and Jiang (2022), metadiscourse has emerged as one of the most popular methods for examining texts, as evidenced by 29,500 publications containing the term 'metadiscourse' that is returned by a Google Scholar search, 11,000 of which were published in the recent five years. From the last decade, researchers have investigated metadiscourse markers in various genres which includes academic writing (Hyland 2010, Alshahrani 2015, Gezegİn and Melike 2020, persuasive writing (Noorian and Biria 2017, Korau and Aliyu 2020), research articles (Gillaerts and Van de Velde 2010, Sultan 2011, Cao and Hu 2014, Salek 2014, writing of the EFL learners (Jalilifar andAlipour 2007, Rad 2020), news reports (Boshrabadi et al 2014), news articles (Yazdani et al 2014), news editorials (Kuhi and Mojood 2014), opinion columns ( Dafouz-Milne 2008), opinion writings on online platforms (Biri 2018), travel vlogs (Huang et al 2020), advertising (Fuertes-Olivera et al 2001) etc.…”
Section: 6mentioning
confidence: 99%
“…Huang et al (2020) investigated the interactional metadiscourse in English travel blogs. This study explored how travel bloggers use interactional metadiscourse in their blogs to interact with their readers.…”
mentioning
confidence: 99%